Pengaruh Kebijakan Dividen Dan Risiko Kredit Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Islamy, Zahra Nadhira; Petra, Berta Agus; Pratiwi, Nila (Jurnal Ekonomi dan Bisnis Digital, 2026)
Maximizing firm value is very important for a company, because maximizing firm value also means maximizing shareholder wealth, which is the main objective of the company. This study aims to examine the effect of dividend policy and credit risk on firm value, with profitability as an intervening variable, in banking companies listed on the Indonesia Stock Exchange. This research uses a quantitative method. The population of this study consists of all banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The results of this study indicate that dividend policy and credit risk partially has no significant effect on firm value. Dividend policy partially has no significant effect on profitability. Credit risk partially has a positive and significant effect on profitability. Profitability partially has a positive and significant effect on firm value. Dividend policy can partially affect firm value through profitability as a mediating variable. Meanwhile, credit risk cannot partially affect firm value through profitability as a mediating variable.